Pengaruh Perbandingan Kecambah Kacang Merah Dan Nanas Terhadap Karakteristik Kimia Dan Sensori Selai - Zebua, Elva Amurita; Agustina, Agustina (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
Jam is a processed food product that is very popular with the community. The nutritional and sensory value of jam can be improved by use red bean sprouts and pineapple as raw material to making jam. The purpose of this study was to determine the effect of ratio of red kidney bean sprouts and pinneaple on chemical and sensory of jam. This research was conducted by a one-factor completely randomized design, that was the ratio of red kidney bean sprouts and pineapple (P) which consisted of 5 levels, i.e. P1 (0%: 100%), P2 (25%: 75%), P3 (50%: 50%). ), P4 (75%: 25%), and P5 (100%: 0%) with three repetitions. The results showed that the ratio of red kidney bean sprouts and pineapple had a significantly different effect (P <0.05) on water content, protein content, fiber content, vitamin C content, organoleptic value of color, flavor and taste, and had no significant effect (P>0,05) on ash content, total sugar, and organoleptic value of spreadability. The enhancement of persentase of red kidney bean sprout will increase the protein content and fiber content of the jam. The enhancement of percentage of pineapple will increase the moisture content, vitamin C content, organoleptic value of color, flaver, and taste of jam.Keywords:red kidney bean sprouts, pineapple, jam